1990
DOI: 10.1128/aac.34.6.958
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of ampicillin and sulbactam in the lower airways during respiratory infections

Abstract: We studied the penetration of ampicillin-sulbactam in the alveolar lining fluid (ALF) of eight patients after intravenous administration of 2,000 mg of ampicillin and 1,000 mg of sulbactam three times daily over 30 min. Bronchoalveolar lavage was performed on day 3, 30 min after the end of the morning drug administration. The mean penetration ratios (i.e., the ratios of the concentrations in ALF versus those in serum) were 53% (standard error, 12%) and 611% (standard error 31%) for ampicillin and sulbactam, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…It has been shown previously that ␤-lactamase inhibitors, sulbactam in particular, have intrinsic activity against A. baumannii (1,12,16,27,29). The activity of ␤-lactam-␤-lactamase inhibitor combinations used at a fixed ratio of ␤-lactam to inhibitor is reflected mainly by the MICs of the respective inhibitors alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown previously that ␤-lactamase inhibitors, sulbactam in particular, have intrinsic activity against A. baumannii (1,12,16,27,29). The activity of ␤-lactam-␤-lactamase inhibitor combinations used at a fixed ratio of ␤-lactam to inhibitor is reflected mainly by the MICs of the respective inhibitors alone.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the intrinsic activity of the inhibitors and not to ␤-lactamase inhibition (7). Sulbactam has good intrinsic antimicrobial activity against multidrug-resistant Acinetobacter strains at concentrations readily achievable in human serum (29) and may therefore have some therapeutic implications in the treatment of infections caused by multidrug-resistant A. baumannii infections. However, A. baumannii strains with elevated sulbactam MICs (Ն32 mg/liter) exist, and the majority of these strains were outbreak related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulbactam has been reported superior to clavulanic acid and tazobactam and may represent an alternative treatment option for infections due to multiresistant organisms [36]. It has reported that sulbactam has good intrinsic antimicrobial activity against multidrug-resistant Acinetobacter strains at concentrations readily achievable in human serum and may therefore have some therapeutic implications in the treatment of infections caused by multidrug-resistant A. baumannii infections whereas tazobactam and clavulanic acid were only moderately active or inactive [37].…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations in ELF were well correlated with concentrations in plasma, with mean ratios of 10.8 and 6.05% in groups A and B, respectively. Previous studies have evaluated the penetration of antibiotics into the ELF with very different results: the ratios of concentrations in ELF to concentrations in serum were 17% for roxithromycin (3), 53% for ampicillin, 51% for sulbactam (16), and 50% for tobramycin (2). These variations could have resulted from two main differences in these studies.…”
Section: Discussionmentioning
confidence: 70%